PENERAPAN MEDIA AUDIO VISUAL SEBAGAI STRATEGI PENINGKATAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK - Dadang Sahroni; Asep Suhendar; Maudi Meilani; Siti Masruroh; Wina Siti Sawanah (STKIP Pesisir Selatan, 2024)
This research was motivated by the importance of using innovative learning media to improve students’ learning motivation in the Akidah Akhlak subject. The low level of students’ interest and participation in the learning process became one of the challenges that needed to be addressed through the use of audio-visual media. This study aimed to analyze the implementation of audio-visual media in Akidah Akhlak learning, measure the level of learning motivation among seventh-grade students, and determine the effect of audio-visual media on students’ learning motivation at MTsS Al-Istiqomah Caringin Bogor. The research employed a quantitative approach with an associative research method. The population consisted of all seventh-grade students of MTsS Al-Istiqomah Caringin Bogor, while the sample was selected using the Simple Random Sampling technique. The results showed that the implementation of audio-visual media in Akidah Akhlak learning was categorized as good, while students’ learning motivation was categorized as high. Furthermore, the hypothesis testing indicated that there was a significant effect of audio-visual media on students’ learning motivation, as evidenced by a significance value of less than 0.05 and the coefficient of determination value, which demonstrated that audio-visual media contributed positively to improving students’ learning motivation.